Knowledge Mobilized in Teacher–Student Interactions in PE in Difficult Vocational High School Classes: Enacted Knowledge - Girard, Amélina; Vors, Olivier (Frontiers in Psychology, 2021)
Introduction Our study aims to analyse the enactive knowledge mobilised during teacher-student interactions in physical education lessons with difficult classes in vocational high school. These classes are considered 'difficult' because they concentrate a large number of pupils who are referred to them because they have no choice (Caille, 2014). This lack of choice makes it difficult for these pupils to engage in school work and is the cause of deviant behaviour and school drop-out (Arrighi and Gasquet, 2010). Methode This study was conducted within the methodological and theoretical research programme of the Course of Action. We analysed the individual activity of nine teachers and 18 students during a PE lesson by collecting audio-visual data and conducting self-confrontation interviews. These data were processed in several stages: transcription, identification and typification of the components of the experience. Results The results show mutual active knowledge between the teacher and the “difficult” students: emerging from the context, anchored in a dynamic of experience, coupled with the actor’s concerns. The teacher classifies the students’ profiles according to their reaction to authority and their difficulties, by spotting students’ “thermometers” of the class climate. Some of the students’ knowledge is coupled with their concerns to avoid boredom, to avoid trouble with the teacher and to avoid trouble with their friends.